Impact of pre‐hospital antibiotic use on community‐acquired pneumonia. (10th February 2014) - Simonetti, A. F.; Viasus, D.; Garcia‐Vidal, C.; Grillo, S.; Molero, L.; Dorca, J.; Carratalà, J.; Paul, M.
Abstract Information on the influence of pre‐hospital antibiotic treatment on the causative organisms, clinical features and outcomes of patients with community‐acquired pneumonia (CAP) remains scarce. We performed an observational study of a prospective cohort of non‐immunosuppressed adults hospitalized with CAP between 2003 and 2012. Patients were divided into two groups: those who had received pre‐hospital antibiotic treatment for the same episode of CAP and those who had not. A propensity score was used to match patients. Of 2179 consecutive episodes of CAP, 376 (17.3%) occurred in patients who had received pre‐hospital antibiotic treatment. After propensity score matching, Legionella pneumophila was more frequently identified in patients with pre‐hospital antibiotic treatment, while Streptococcus pneumoniae was less common (p <0.001 and p <0.001, respectively). Bacteraemia was less frequent in pre‐treated patients (p 0.01). The frequency of positive sputum culture and the sensitivity and specificity of the pneumococcal urinary antigen test for diagnosing pneumococcal pneumonia were similar in the two groups. Patients with pre‐hospital antibiotic treatment were less likely to present fever (p 0.02) or leucocytosis (p 0.001). Conversely, chest X‐ray cavitation was more frequent in these patients (p 0.04). No significant differences were found in the frequency of patients classified into high‐risk Pneumonia Severity Index classes, in intensive care unit admission, or in 30‐day mortality between the groups. In conclusion, L. pneumophila occurrence was nearly three times higher in patients who received pre‐hospital antibiotics. After a propensity‐adjusted analysis, no significant differences were found in prognosis between study groups. Pre‐hospital antibiotic use should be considered when choosing aetiological diagnostic tests and empirical antibiotic therapy in patients with CAP.